AB0467 Influence of Rituximab Retreatment on Sustained Response in Patients with Rheumatoid Arthritis Enrolled in the us Corrona Registry. (9th June 2015) - Harrold, L.R.; John, A.; Reed, G.W.; Karki, C.; Magner, R.; Kremer, J.M.; Shewade, A.; Greenberg, J.D.
Abstract : Background: The goal of treatment for patients with rheumatoid arthritis (RA) is to reduce and maintain disease activity to low disease activity (LDA) or remission. However, there is little information available regarding the likelihood of sustained response once LDA/remission has been achieved, as well as what effect rituximab retreatment has on sustained response. Objectives: The objective of this analysis was to examine factors associated with sustained response in patients with RA who were treated with rituximab in the US Corrona registry. Methods: Patients with RA who initiated rituximab while in moderate or high disease activity (Clinical Disease Activity Index [CDAI] >10) and who subsequently achieved LDA/remission (CDAI ≤10) within 12 months of their last rituximab infusion were identified from the Corrona registry and included in this analysis. Patients were followed until they experienced loss of response (defined as CDAI >10), initiated another biologic or small molecule or exited from the registry. Covariates identified at the index date (when LDA/remission was achieved) included demographic and clinical characteristics, prior medications and concomitant steroid and conventional synthetic disease modifying anti-rheumatic drug (csDMARD) use. Covariates ascertained at the time of rituximab initiation included functional status, baseline CDAI, patient-reported pain and time to achieve LDA/remission. Time-varying covariates of interest included the rate of rituximab retreatment, as well as number of prednisone dose increases and initiations of csDMARDs over time. Survival analyses and Cox proportional hazard regression models were performed to estimate the overall likelihood of sustained response following rituximab treatment and associations between covariates of interest and sustained response. The primary estimate of interest was the hazard ratio or loss of response for rituximab retreatment. Results: Of the 1184 patients who initiated rituximab and had ≥1 follow-up appointment in Corrona, a total of 306 patients subsequently achieved CDAI LDA/remission within 12 months of the last infusion. Most patients were female (75.8%) with a median (IQR) age of 60 (52-68) years and received prior csDMARDs (median [IQR], 2 [1-3]); over 84% of patients had received ≥2 prior biologics. The median (IQR) time to achieve LDA/remission was 5 (3-10) months. Of the 306 patients included in the final study population, 104 patients received rituximab retreatments at a median (IQR) rate of 1.01 (0.71-1.36) retreatments per year. Twelve months following achievement of LDA/remission, 49.2% of patients maintained this response. In unadjusted and adjusted models (Table ), rituximab retreatment was associated with a significantly reduced likelihood of loss of response (45% reduction), while prednisone dose increases ≥7.5 mg and prior non-anti–tumor necrosis factor agent use increased it. Conclusions: Retreatment with rituximab was associated with a significantly greater sustained response in patients who have achieved LDA/remission on the medication, while low to moderate prednisone increases and prior non-anti–tumor necrosis factor agent use reduced it. Acknowledgements: This study is sponsored by Corrona, LLC. Disclosure of Interest: L. Harrold Grant/research support from: Corrona, LLC, A. John Employee of: Genentech, Inc, G. Reed Employee of: Corrona, LLC, C. Karki Employee of: Corrona, LLC, R. Magner Employee of: University of Massachusetts Medical School, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: Genentech, Inc, Consultant for: Genentech, Inc, Employee of: Corrona, LLC, A. Shewade Employee of: Genentech, Inc, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Novartis and Pfizer, Employee of: Corrona, LLC